Kombinasi Tetrahidrokurkumin dan Cyanidine-3-O-β-glucoside sebagai Terapi Fitokimia Asma Anak melalui Penghambatan IL-4Rα-STAT6 dan Sitokin Proinflamasi - Afid Brilliana Putra; Muhammad Ilham Dhiya Rakasiwi; Ihya Fakhrurizal Amin (Fakultas Kedokteran Universitas Riau, 2022)
Asthma is chronic inflammatory disease experienced mostly by children with prevalence of 4.5% in Indonesia. Asthma puts burden on sufferers because of the long duration of treatment. However, prolonged inhaled corticosteroids use in certain doses can cause side effects. Tetrahydrocurcumin (THC) is metabolite of curcumin and has higher bioavailability than its precursor molecules. THC has been shown to significantly reduce leukocyte infiltration, as well as inhibit inflammation through IL-4Rα pathway and decrease GATA3 expression. The same effect is obtained from Cyanidine-3-O-β-glucoside (Cy-3-g). The anti-inflammatory effect of those combination can be used as alternative phytochemical therapy to treat asthma in children.